Organizational and pedagogical conditions of management of the education of future teachers in the conditions of digitalization of education - Prokopenko, Alona (My University, 2022)
Наукове дослідження щодо процесу едукації МУ в умовах діджиталізації освіти спрямовує автора на необхідність вивчення питання реалізації управління процесом едукації. Для цього потрібно дослідити проблему забезпечення організаційно-педагогічних умов та висвітлити авторське бачення розв’язання цієї проблеми. Здійснено вивчення та аналіз наукових досліджень вітчизняних та зарубіжних науковців щодо розуміння проблеми педагогічних та організаційно-педагогічних умов забезпечення процесу едукації МУ, а також організації цих умов під час діджиталізації освітнього простору вищої освіти. Автором зазначено, що процес організації та управління едукацією МУ повинен передбачати кілька особливостей. Серед них виокремлено: мотиваційна та вікова складова, яка спрямована на активність та цілеспрямованість МУ під час едукації; взаємодія із стейкхолдерами, які висувають актуальні вимоги до конкурентноспроможності випускників, а й від так коригують освітні програми, сприяють поглибленню передбачуваних результатів едукації МУ; урахування особливостей умов діджиталізації освіти, що пов’язані із формування готовності МУ до використання інформаційно-комунікативних засобів едукації у своїй майбутній професійній діяльності. У статті досліджено дві організаційно-педагогічні умови управляння едукацією МУ в сучасних умовах діджиталізації вищої освіти, а саме модернізація діяльності управлінського кластера та забезпечення ефективності функціонування студентоцентриського середовища. Визначено, що ці умови ґрунтуються на формуванні практичного досвіду кожного майбутнього фахівця, який готовий до освітніх та наукових викликів сьогодення, а також здатен до самоосвіти в умовах діджиталізації. Так ці організаційно-педагогічні умови сприяють забезпечення продуктивне управління едукацією МУ в умовах діджиталізації освіти. A scientific study of the educational process of future teachers (FT) in the conditions of digitalization of education directs the author to the need to study the issue of implementing the management of the educational process. To solve this issue, it is necessary to investigate the problem of ensuring organizational and pedagogical conditions and highlight the author's vision of solving this problem. It is carried out the study and analysis of scientific research by domestic and foreign scientists regarding the understanding of the problem of pedagogical and organizational-pedagogical conditions for ensuring the educational process of FT, and the organization of these conditions during the digitalization of the educational space of higher education. The author states that the process of organizing and managing the education of future teachers should include several features. Among them, the following are highlighted: the motivational and age component, which is aimed at the activity and purposefulness of FT during education; interaction with stakeholders who put forth actual requirements for the competitiveness of graduates, as well as adjust educational programs accordingly, contribute to the deepening of the expected results of the education of FT; taking into account the peculiarities of the conditions of digitization of education, which are related to the formation of the readiness of FT to use informational and communicative means of education in their future professional activities. The article examines two organizational and pedagogical conditions for managing the education of FT in the modern conditions of digitization of higher education, namely, the modernization of the management cluster and ensuring the effectiveness of the student-centered environment. It is determined that these conditions are based on the formation of practical experience of each future specialist who is ready for the educational and scientific challenges of the present time, and is also capable of self-education in the conditions of digitalization. Thus, these organizational and pedagogical conditions contribute to the provision of productive management of the education of FT in the conditions of digitalization of education.
Keywords: умови; діджиталізація; діджиталізація освіти; майбутній учитель (МУ); едукація; управління; управління едукацією; conditions; digitalization; digitalization of education; future teacher (FT); education; management; management education